2018
DOI: 10.1111/codi.13715
|View full text |Cite
|
Sign up to set email alerts
|

Final results of a European, multicentre, prospective, observational study of Permacol™ collagen paste injection for the treatment of anal fistula

Abstract: Permacol paste provides a promising sphincter-preserving treatment for anal fistulas with minimal adverse side-effects. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 20 publications
2
26
2
Order By: Relevance
“…Our overall healing rate was disappointing compared with the results of similar studies, which reported healing rates ranging from 47.6% to 82.3%. 14,[32][33][34] This difference might be explained by the heterogeneous populations selected in these studies, making it impossible to compare their clinical outcomes with our results. Other possible explanations for the discrepancy in the reported success rates might be related to differences in the technique of closure of the internal opening of the fistula.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Our overall healing rate was disappointing compared with the results of similar studies, which reported healing rates ranging from 47.6% to 82.3%. 14,[32][33][34] This difference might be explained by the heterogeneous populations selected in these studies, making it impossible to compare their clinical outcomes with our results. Other possible explanations for the discrepancy in the reported success rates might be related to differences in the technique of closure of the internal opening of the fistula.…”
Section: Discussionmentioning
confidence: 81%
“…31 When placed into the fistula tract, the Permacol paste occludes the tract without requiring sphincter division, thus eliminating the risk of subsequent incontinence. 14,[32][33][34] Implantation of the paste is a technically simple procedure that requires only a minimal amount of operating room time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence so far suggests that biomedical products manufactured using animal-derived collagens do not present any significant danger to the human recipients [46]. However, some concerns still exist about the potential negative impacts of non-collagenous molecules that co-purify with animal-derived collagen.…”
Section: Potential Limitations Of Collagens Isolated From the Naturalmentioning
confidence: 99%